ASGRT – Automated Report Generation System - GJorgjevikj, Dejan; Madjarov, Gjorgji; CHorbev, Ivan; Angelovski, Martin; Georgiev, Marjan; Dikovski, Bojan (Springer Berlin Heidelberg, 2011)
We have come to a point in time when there is an abundance of database usage in almost all aspects of our lives. However, most of the end users have neither the knowledge nor the need to manage the databases. Even more important, they are unable to generate the ever changing reports they need, based on the data in their databases. Our Applicative Solution for Generating Reports from Templates (ASGRT) tries to deal efficiently with this issue. It has a simple yet effective architectural design aimed to give power to the more experienced administrators and simplicity to common end users, to generate reports with their own criteria and design, from their databases. The presented software enables creation of templates containing text and tags that are recognized and substituted by values retrieved from the database, therefore enabling creation of customized reports with varying ease of use and flexibility.